Hedonic and utilitarian benefits as determinants of the application continuance intention in location-based applications: the mediating role of satisfaction - Akel, Gökhan; Armağan, Ece (Multimedia tools and applications, 2021)
The increase in the number of social media users and smartphone usage has a positive relationship with the diversity of applications. People use mobile applications that provide location-based service either directly or indirectly to share location with their smartphones. With the increase in the use of applications that determine location information by determining location information on mobile devices, mobile applications have become an important research area for user behavior. These applications are also utilized by users for communication and socialization purposes. The literature has usually focused on popular social media applications and studies on location-based applications (LBAs) have been insufficient. In this study, we investigate the impact of location-based services, such as Swarm and Foursquare. This study uses the technology acceptance model (TAM) and the expectation confirmation model (ECM) to understand why users continue using mobile applications. This article examines the role of hedonic comprised of application aesthetics and perceived enjoyment and utilitarian benefits (comprised of application quality and application utility) for consumer behavior in the development of application markets on satisfaction and application continuance intention. Besides, we show the benefits of the strongest effect on application users. By using the mediation satisfaction effect between hedonic and utilitarian benefits; we test the application continuance intention with regression analyses and the Sobel test. We surveyed young subjects as our sapling frame who regularly use mobile applications. We collected data from 400 users by convenience sampling method to test our hypotheses. Given our findings, we show that utilitarian and hedonic benefits are positively related to the application continuance intention. Besides, we show that satisfaction significantly mediates the relationship between hedonic/utilitarian benefits and application continuance intention. Since the main purpose of the application developers is using the application per se in the long term, they need to focus chiefly on user satisfaction. We also show that determining the relevant factors that affect application continuance intention positively is important for the businesses in a competitive environment.